Inequalities versus Utilization: Factors Predicting Access to Healthcare in Ghana - Dominic Buer Boyetey (Centre for Behaviour and Wellness Advocacy, 2016)
Universal access to health care remains a significant source of inequality especially among vulnerable groups. Challenges such as lack of insurance coverage, absence of certain types of care, as well as high individual financial care cost can be blamed for the growing inequality in the healthcare sector. The concern is worrying especially when people are denied care. It is in this light that the study set to find out what factors are likely to impact the chances of access to health care, so far as the Ghana Demographic and Health Survey Data 2014 data are concerned, particularly to examine the differences in access to healthcare in connection with varying income groups, educational levels and residential locations. The study relied on the logistic regression analysis to establish that people with some level of education have greater chances of accessing health care compared with those without education. Also chances of access to health care in the sample were high for people in the lower quartile and upper quartile of the household wealth index and a local minimum for those in the middle class. It became evident also that increased number of people with NHIS or PHIS or combination of cash with NHIS or PHIS will give rise to a corresponding increment in the probability of gaining access to health care.